CHILDHOOD SARCOIDOSIS - Alper Soylu,; Mehmet Atilla Türkmen,; Salih Kavukçu, (Archives of Rheumatology, 2005)
Sarcoidosis is a systemic noncaseating granulomatous disorder of unknown origin. It is rare in children. There are two forms of juvenile sarcoidosis according to the age of onset. The early-onset form in the first 4-5 years of life is usually characterized by the triad of uveitis, arthritis and rash. The older children and adolescents have a form of sarcoid that is similar to the adult one with pulmonary infiltrates, hilar adenopathy, and systemic features such as weight loss and fever. The diagnosis of sarcoidosis is based on the demonstration of non-caseating granulomata in one or more organs in the setting of consistent radiographic or clinical findings. The most commonly involved organ systems are respiratory tract, lymphatic system, skin, eyes, nervous system, kidney, liver, heart and blood vessels and musculoskeletal system. Symptoms of early onset sarcoidosis characterized by arthritis, uveitis and skin eruptions mimic those of systemic type juvenile rheumatoid arthritis. Skin biopsy may be useful for differential diagnosis. Corticosteroids and methotrexate are usually used as therapeutic agents for juvenile sarcoidosis.